DIABETES MELITUS BECOME A HEALING DISEASE IN COVID-19 PATIENTS (SYSTEMATIC REVIEW) - WAHYU WAHDANA; Hotma Rumoharbo; Murtiningsih Murtiningsih; Yayat Suryati; Hikmat Rudyana (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Background: Diabetes mellitus (DM) is a chronic disease characterized by high blood sugar levels and is one of the most commonly reported comorbidities and is a risk factor for increasing the severity of Covid-19 infection. Diabetes is the second comorbidity that is often found in Covid-19 patients in Indonesia with 35.5% cases, 24.1% recovery, and 10.6% death. This study aims to conduct a systematic review based on the results of studies that have been published so far about DM disease complicating healing, exacerbating disease conditions, and causing death in Covid-19 patients.Method: The research used systematic review on several electronic databases on the subjects of Covid-19 patients with diabetes who had changed disease conditions. Search for articles using the PEOS strategy and using the keyword "COVID-19 OR SARS-CoV-2 OR Coronavirus AND Diabetes". Data were analyzed descriptively narrative.Result: The identification results obtained as many as 3,381 articles, there were 34 articles according to the criteria and were synthesized and analyzed. DM makes healing difficult and worsens disease conditions in Covid-19 patients because it is associated with the development of more severe Covid-19 disease conditions, increased sugar levels, the effects of ACE2 and DPP-4, the occurrence of ARDS, critical conditions, care in ICU, and risk of death. which is higher than non-diabetic patients, as well as the addition of other comorbidities such as hypertension in DM patients.Conclusion: Diabetes can make healing difficult, worsen disease conditions, and cause death in Covid-19 patients. Further research is needed to assess and investigate the role of glycemic control prior to Covid-19 infection.